Development of Greenness Index as an evaluation tool to assess reagents: Evaluation based on SDS (Safety Data Sheet) information. (August 2016) - Shen, Yang; Lo, Chi; Nagaraj, D.R.; Farinato, Raymond; Essenfeld, Amy; Somasundaran, P.
Highlights: Greenness Index aims to provides comprehensive assessments of reagents. When SDS is used as the data source, Greenness Index gives preliminary evaluations. Mathematical model and calculations have been developed for each section on SDS. A hierarchy of spider-diagrams is used to visualize greenness. PAX is set as an example evaluated by Greenness Index . Abstract: Evaluation of the impacts of reagents on SHE (safety, health, and the environment) is crucial for industries, regulatory agencies, and governments; however, it is a nontrivial task and there has not been universal acceptance of metrics or tools for this purpose. We have been developing an evaluation tool called Greenness Index to provide a holistic assessment of reagents used in various industries. Analysis by means of this tool is based on information found in reagent SDSs (Safety Data Sheets) plus metrics for various consequences when the reagent is used in a particular application. SDSs contain information on the various properties of a reagent and how it impacts SHE from cradle to grave; however, these summaries rarely consider the multifarious possibilities of how the reagent may transform during use in an application. Including such features in a more complete evaluation of the SHE impact of a reagent is the ultimate goal of our efforts to develop Greenness Index. Efforts reported here are in the preliminary step of representing the panoply of SHE information found in SDSs in a manner that allows a more holistic, multi-parametric comparison of reagents. Five clusters (Health Impact, General Properties, Odor, Fire Safety, and Stability) of attributes that are combined to form a total evaluation were created based on widely accepted sustainability guidelines such as the Green Chemistry 12 Principles and Green Engineering 12 Principles. Sorting and binning algorithms were developed to quantify each attribute and cluster of attributes, resulting in quantitative scores for each. Scores are displayed graphically to help visualize the relative Greenness of the reagent. Displays are in the form of a hierarchy of spider-diagrams. This Greenness Index method has been applied in a variety of instances to specific reagents used in various industries such as mineral processing and personal care. Greenness Index analysis of PAX (Potassium Amyl Xanthate), commonly used as a flotation reagent in mineral processing, is described here as an example. Results from such an analysis can be incorporated into a decision making process that facilitates the selection of greener reagents and provides valuable insights to improve and develop sustainable practices.